Optimization of Distribution Routes for Srikandi MSMES in Samarinda Using VRP Method: A Comparative Study of CWS and CFRS - Hasdi, Rani Anjelika; Isharyani, Muriani Emelda; Wahyuda (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2025)
This research aims to optimize the distribution route of snack products for UMKM Srikandi Samarinda using the Vehicle Routing Problem (VRP) approach. The main issues are high travel distances, fuel costs, and delivery times due to the absence of route optimization. Two VRP solution methods are compared: Clarke and Wright Savings (CWS) and Cluster First Route Second (CFRS). The CWS method reduces travel distance by combining routes based on the highest distance savings between customer points, maximizing vehicle capacity. The CFRS method groups customer points into clusters using the Sweep algorithm based on proximity to the depot and determines the visit sequence within each cluster using the Nearest Neighbor method. Results show CFRS achieves better distribution efficiency. On the first route, CFRS traveled 94.1 km using 7 liters of fuel (Rp88,550), while CWS traveled 113.7 km using 9 liters (Rp113,850). On the second route, both methods covered about 75 km with similar fuel costs (Rp75,900), but CFRS was more consistent in savings, with the highest efficiency at 63.28%. With a total fuel cost saving of Rp140,939 compared to the initial condition, CFRS is recommended as the optimal solution, capable of reducing distance, operational costs, and improving delivery effectiveness.